Musical Intimacy, Model Citizenship, and Sufism in the Life of Niyazi Sayın. (May 2022) - Senay, Banu; Houston, Christopher
Abstract: Niyazi Sayın is an Istanbul-born ney (reed flute) virtuoso, and the most acclaimed musician of a musical tradition controversially called "Ottoman-Turkish classical music." Now 94 years old, Sayın has been called insan-i kamil (a perfect human), kutb-ı nayi, (the musical spiritual axis of his age), and hezarfen (master of a thousand arts). What do such titles mean? Building upon the work of Martin Stokes on popular music and its fashioning of intimate publics, this paper explores Sayın's musical life. We argue that it provides an exemplary expression of cultural intimacy for listeners and students, one that (as reflected in his titles) demonstrates a particular way of becoming a person, a Muslim, and a model citizen. In contrast with more official constructions of citizenship, as well as with the political neo-Ottomanism of the Justice and Development Party (AKP), Sayın's life and music open up alternative possibilities of self-alteration for those who engage with it.